Associations between gut microbiota and immune status in untreated B-cell lymphoma patients - Zhou, Jingxin; Yao, Jinrong; Hu, Na; Su, Jing (Frontiers in Immunology, 2025)
BackgroundEmerging evidence links gut microbiota to tumorigenesis via immune modulation, though subtype-specific microbial signatures in B-cell lymphomas remain unclear. This study explores microbiota-immune interactions across lymphoma subtypes to inform microbiota-targeted therapies.MethodsTwenty-seven treatment-naive B-cell lymphoma patients (8 DLBCL, 5 SLL, 5 FL, 7 MZL, 2 WM) and 20 HCs were enrolled. Fecal 16S rDNA sequencing, flow cytometry for immune cell subsets, and ELISA for cytokines/immunoglobulins were performed. Microbiota differences and correlations with immune parameters were analyzed.ResultsB-cell lymphoma patients showed lower fecal microbiota richness/evenness (P<0.05), with increased Actinobacteriota, Bacilli, Enterobacteriaceae and decreased Bacteroidetes. Small B-cell lymphoma and DLBCL exhibited distinct flora: Selenomonadaceae/Actinobacteriota dominated in DLBCL, while Enterobacteriaceae prevailed in small B-cell subtypes. Correlations showed Enterobacteriaceae positively linked to Th cells/PCT/TNF and negatively to IL-10 in small B-cell lymphoma; Actinobacteriota correlated with B/T cells/Treg/IFN-β and inversely with IL-2/IL-4/CD8+T cells.ConclusionsThis study identifies distinct patterns of gut microbiota dysbiosis across B-cell lymphoma subtypes and explores their correlations with host immune parameters.